Agenda 1996 Anwar lawan Mahathir - Mohd. Sayuti Omar, 1960- (Kuala Lumpur : Tinta Merah, 1995)
Politics and government in Malaysia; rivalry between Anwar Ibrahim, the deputy prime minister, and Mahathir.
In Malay.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Malaysia -- Politics and government